ENVIRONMENT: sustainability as a means to eradicate environmental degradation - Mariano, Nilson; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
Environmental degradation is a process that has been discussed and addressed for a long time, the level of environmental degradation has been increasing significantly, and the result of this is the destruction of natural resources, the ecosystem, biodiversity and the entire system that involves the environment. environment. Sustainability is essential and seeks forms of balance between all the principles of human needs and the preservation of natural resources, also encompassing the environment, and precisely comes to change and guarantee a positive and adequate scenario in relation to the way they are being used and exploited. Based on the subject discussed, the present work is justified based on the current scenario of degradation and environmental wear, and aims to demonstrate the importance of sustainability and the means of mitigation through them employed to society, aiming at the eradication of environmental wear , as well as the inadequate and radical exploitation of natural resources, results obtained through the bibliographic review method, scientific articles, books, magazines and electronic sites that are related to the subject, thus concluding that the approach of sustainability as a way of mitigating the environmental wear is an excellent alternative, based on the necessary, cautious and rapid change that needs to be adopted globally.